Post-pandemic Economics and Health Equity; Comment on "Ensuring Global Health Equity in a Post-pandemic Economy" - Karime Chahuán-Jiménez (Kerman University of Medical Sciences, 2023)
This article aims to compare the foundations of the post-pandemic economy and its impact on health equity, according to Labonté with the economics theory. The methodology developed is based on bibliometrics analysis, the documents, and specifications for a cluster of concepts, allowing deepened exposure of Labonté, complementing with the latest publications on the post-pandemic economy. Finally, the results agreed with Labonté about to economic development for achieving an economy that allows health equity considering sustainable development and the possibility of achieving the livelihood of Green New Deal as a basis.